THE IMPLEMENTATION OF STUDENTS' CHARACTER BUILDING THROUGH THE SCHOOL LITERACY MOVEMENT AT SMP NEGERI 1 SENGKANG, WAJO REGENCY - Jamil, Jamil; Asik, Nur; Mardiana, Mardiana (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This study aims to determine the implementation of character building of students through the school literacy movement at SMP Negeri 1 Sengkang, Wajo Regency. This research is classified as qualitative research with historical, phenomenological, pedagogical, sociological, and psychological approaches. Researchers conducted interviews with teachers, education staff, resource persons, and students at SMP Negeri 1 Sengkang, Wajo Regency, to obtain data in the field. In addition, direct observations are also made on the material and stages of implementing activities. The data obtained from interviews and direct observations were analyzed by qualitative methods to determine the implementation, supporting and inhibiting factors, and efforts to overcome the inhibiting factors. The results showed that the formation of student character through the school literacy movement at SMP Negeri 1 Sengkang, Wajo Regency, was carried out integrally in implementing 15-minute habituation to reading. They responded to reading content through book reading journals, optimizing literacy facilities and a text-rich environment, and selecting reading books. The formation of his character is seen in the habituation of 15 minutes of reading. The optimization of literacy means a text-rich environment that gives birth to a character of curiosity and love to read, responding to the content of readings through book reading journals, and the selection of reading books that give birth to honest characters. The supporting factors are the positive response and good cooperation from school stakeholders, optimization of library services, and the role of parents/guardians through the collaboration of school committees.